Application of neural networks to the detection of fraud in workers’ compensation insurance : application to a Portuguese insurer - Oliveira, Inês Bruno de (2018)
Project Work presented as the partial requirement for obtaining a Master's degree in Statistics and Information Management, specialization in Risk Analysis and Management